2022
DOI: 10.3389/fpls.2022.1024898
|View full text |Cite
|
Sign up to set email alerts
|

Crop yield and water use efficiency in response to long-term diversified crop rotations

Abstract: Crop production and water productivity may be impacted by diverse crop rotation and management practices. A field study was conducted from 2017-2020 in the Loess Plateau to evaluate the effects of crop rotation sequences on pre-planting and post-harvest soil water storage (SWS), annualized crop yield, water use, and water productivity. Crops in rotation included oil flax (Linum usitatissimum L.) (F), wheat (Triticum aestivum L.) (W), potato (Solanum tuberosum L.) (P). Twelve 4-year-cycle crop rotation treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This finding is contradictory with [54], who found that the water consumption of pepper plants grown in perlite was significantly higher than that of plants grown in rice straw. Water use efficiency (WUE) is usually calculated based on the fruit yield given per unit of water consumed by the crop [58]. The protected culture industry is continually seeking alternative substrates that are locally available, economically feasible, and sustainable, to replace conventional growing media sources [59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is contradictory with [54], who found that the water consumption of pepper plants grown in perlite was significantly higher than that of plants grown in rice straw. Water use efficiency (WUE) is usually calculated based on the fruit yield given per unit of water consumed by the crop [58]. The protected culture industry is continually seeking alternative substrates that are locally available, economically feasible, and sustainable, to replace conventional growing media sources [59].…”
Section: Resultsmentioning
confidence: 99%
“…Water use efficiency (WUE) is usually calculated based on the fruit yield given per unit of water consumed by the crop [ 58 ]. The protected culture industry is continually seeking alternative substrates that are locally available, economically feasible, and sustainable, to replace conventional growing media sources [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is worth noting that while crop rotation (T2, T4) and crop rotation in combined with quicklime application (T3, T5) are superior to continuous cropping (T1) in guaranteeing peanut yields, there is a tendency for the yield advantages of these four cultivation managements tend to decline year after year. It has been shown that different crop rotation patterns have different soil mineral nutrient content and soil water retention capacity due to different cultivated crops (Zhang et al, 2019;Cui and Yan, 2022). Although crop rotation plays an important role in improving the multifunctionality of soil ecosystems and maintaining the yield stability of the main crop, for main crop with sensitive mineral fertilizer and water requirements, multi-year crop rotation cannot make up for the differences in mineral fertilizer requirements and water-fertilizer coupling effects of the main crop, and the differences in different crop rotation patterns will decrease with the increase in the number of cropping years (Liu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The diversification of crop rotation and introduction of drought resistant, heat resistant crops and varieties is of importance to establish agricultural sustainability in changing climate (Choukri et al, 2022;Cui et al, 2022;Li et al, 2021). In the context of this investigation, Lens culinaris (lentil) demonstrates exemplary potential as a formidable candidate.…”
Section: Introductionmentioning
confidence: 99%